Tingkat Pengetahuan Masyarakat Tentang DAGUSIBU (Dapatkan, Gunakan, Simpan, Buang) Obat Antibiotik Amoxicillin Di Rt. 03 Rw.01 Kelurahan Prajurit Kulon Kota Mojokerto Periode Februari 2023 - dianita suryaningrum; Widodo Priyanto (Akademi Farmasi Mitra Sehat Mandiri Sidoarjo, 2023)
Abstract Amoxicillin antibiotic drug use is currently a popular phenomenon in the population that contributes to a number of health issues, particularly those connected to drug resistance. Amoxicillin antibiotic drug DAGUSIBU (Get, Use, Save, Dispose) is a program to carry out the Drug Awareness Community Movement. The purpose of this study is to evaluate the level of public awareness of the DAGUSIBU Amoxicillin Antibiotic Drug in Prajurit Kulon Village, Mojokerto City (Rt.03 Rw.01). The approach used in this study is descriptive-analytical observation, with data being collected through validity- and reliabilitytested questionnaires that are then given out to participants. A sample of 75 respondents was used in this study, which was conducted in the neighborhood of RT.03 RW.01 Prajurit Kulon Village, Mojokerto City in this study, spreading questionnaires to respondents and applying purposive sampling to collect data. With 75 respondents, this study was conducted in the neighborhood of RT.03 RW.01 Prajurit Kulon Village, Mojokerto City. The study's results suggest that 56.2% of participants have enough knowledge to